Mapping palliative care provision in European prisons: an EAPC Task Force Survey - Turner, Mary (2021)
Objectives: Prison populations around the world are ageing and numbers are rising, leading to greater demand for palliative care for prisoners approaching the end of life. This paper reports a survey that was undertaken by the European Association for Palliative Care Task Force on mapping palliative care provision for prisoners in Europe. The Task Force was established to begin to address the gap in research knowledge by exploring prison systems and care provision across different countries. Methods: The survey, developed by the Task Force Steering Committee, consisted of 40 questions in six sections. It was completed through online searches; only data that were publicly available on the internet were included. Numerical data were analysed using descriptive statistics, and thematic comparisons were made of free-text data. Findings: The survey was completed for eight countries: Australia, Belgium, Czech Republic, England and Wales, France, Portugal, Scotland and Slovakia. Three main findings are reported here: healthcare and palliative care provision in prisons, deaths in custody and compassionate release. Despite increasing numbers of older prisoners, relatively few prisons provide inpatient care, and only one country has any prisons that provide dedicated palliative care services. Early release on compassionate grounds is extremely rare in most countries. Conclusion: For the principle of equivalence to be adhered to, facilities for sick and dying prisoners need to be improved, or many more people need to be released on compassionate grounds at the end of life. This mapping study has identified key issues in relation to palliative care in prison and provides the basis for further international research.